2009
DOI: 10.1038/ejhg.2009.30
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence data on all Ghent features in a cross-sectional study of 87 adults with proven Marfan syndrome

Abstract: The prevalence of each single feature in the Ghent criteria in patients with Marfan syndrome (MFS) is not known. To elucidate this, a cross-sectional study of 105 adults with presumed MFS was carried out. All patients were examined by the same group of investigators with standardized and complete assessment of all features in the Ghent criteria. Eighty-seven (83%) fulfilled the criteria in 56 different variants. The most prevalent major criterion in Ghent-positive persons was dural ectasia (91%), followed by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 42 publications
0
37
0
Order By: Relevance
“…13 A total of 73 (83.9%) of our Ghent-positive patients had an FBN1 mutation, and 54 (62.1%) had ectopia lentis. As per echocardiographic findings, none of the participants had high pressure in the pulmonary artery.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…13 A total of 73 (83.9%) of our Ghent-positive patients had an FBN1 mutation, and 54 (62.1%) had ectopia lentis. As per echocardiographic findings, none of the participants had high pressure in the pulmonary artery.…”
Section: Resultsmentioning
confidence: 83%
“…[10][11][12][13][14][15][16] For assessing fulfilment of the major cardiovascular criterion in the Ghent nosology, information was collected about previous surgery related to dilatation or dissection of the ascending aorta, and electrocardiographic evidence of dilatation of the ascending aorta was recorded. 1,13 The assessment of fulfilment of the Ghent criteria included sequencing of the entire coding region of the gene FBN1 and searching for large deletions or duplications. 12,13,16 mR or ct of the aorta and pulmonary artery This study was a substudy of the Norwegian Marfan Study.…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 91% of all Ghent-positive patients in our study was found to have DE on the basis of anterior or lateral meningoceles, DSD sacrum Ͼ DSD L4, or the cutoff values at level L5 and S1 of Oosterhof et al 6 Fourteen of 87 patients with MFS (16%) were dependent on DE to fulfill the Ghent criteria, 1 underscoring the importance of assessing the dural sac in individuals investigated for MFS. 2 The dura is 1 of 5 organ systems with major criteria of MFS in the Ghent nosology. Although the dural sac is a soft-tissue structure, DE has been defined to include bony changes of the spine, such as thinning of the cortex of the posterior vertebral elements, widening of the neural foramina, and vertebral scalloping in addition to the presence of a patulous dural sac and anterior meningoceles.…”
Section: Discussionmentioning
confidence: 99%